Heteropaternal superfecundation frequently occurs in multiple‐bearing mob‐mated sheep. (28th April 2020) - Berry, D. P.; Bohan, A.; O'Brien, A. C.; Campion, F. C.; McHugh, N.; Wall, E.
Summary: Heteropaternal superfecundation may be defined as the fertilisation of two or more ova during the same oestrus cycle as a result of more than one coital act from different males; this results in foetuses being born in the same litter of the same age but different paternity. Heteropaternal superfecundation is more likely to occur in poly‐ovulatory species like sheep; moreover, female sheep are often mob‐mated with several rams concurrently, thus providing an opportunity for a given female to be served by multiple males during the same oestrus cycle. The objective of the present study was to determine the frequency of heteropaternal superfecundation in six sheep flocks where most of the ewes, lambs and rams were genotyped. A total of 685 multiple‐birth litters were available where the sire, dam and all lambs were genotyped. Of the 539 pairs of twins included in the analysis, 160 (i.e. 30%) were sired by two different rams. Of the 137 sets of triplets included in the analysis, 73 (i.e. 53%) were sired by more than one ram. Of the nine sets of quadruplets, eight were sired by two rams with the remaining litter being mono‐paternal. The overall incidence of heteropaternal superfecundation among litters was therefore 35%. Given that the incidence of multiple births in these flocks was 65%, heteropaternal superfecundation is expected to be relatively common in sheep; this is especially true as all but two of the litter‐mates were polyzygotic. Genotyping of progeny is one practical solution to identity such individuals.